PERANAN BUDAYA KERJA KOREA SELATAN DALAM MENINGKATKAN KINERJA KARYAWAN Studi pada Karyawan PT. Cheil Jedang Indonesia, Pasuruan - Dita Mayangsari (Fakultas Ilmu Administrasi Universitas Brawijaya, 2014)
This study aimed to determine the work culture of South Korea applied by PT.Cheil Jedang Indonesia, South Korea work culture role in improving the performance of employees and the influence of South Korea work culture on performance of employees. This type of research used a combination of quantitative and qualitative method (mixed method).PT.Cheil Jedang Indonesia Arjosari village located at RT 04 RW 02 Subdistrict Rejoso,Pasuruan.The sampling technique used Slovin’s formula.The results showed that the South Korean work culture emphasizes discipline applied in meeting the targets were flexible and tolerant. Completion of the work processes were ignored as long as the target is reached.The expatriates and employees respect each other so as to form cooperative achievement of the target company.Performance of employees have a very good performance.The role of the South Korean working culture in PT.Cheil Jedang Indonesia has positive effect for employees.The extent to which